Exploration of Endophytic Fungi from Corn in North Sumatra Indonesia and Their Potential as Entomopathogens - Indri Yanil Vajri; Angga Ade Sahfitra; Nur Asyiah Dalimunthe; Rafli Fadillah Lubis; Muhammad Al Fiqri Syuhada (Jurnal Penelitian Pendidikan IPA, 2026)
Entomopathogenic fungi are one of the biological agents that play an important role in controlling insect pests. In addition to being obtained from infected insects and the rhizosphere, this group can also associate as endophytes in plant tissues. This study aims to explore endophytic fungi originating from corn (Zea mays L.) in North Sumatra and evaluate their entomopathogenic potential against insects. Plant samples were collected from corn production centers in the lowlands and middlelands of Deli Serdang and Serdang Bedagai Regencies using a purposive sampling method. Isolation was carried out from healthy plant tissues (roots, stems, and leaves), followed by a pathogenicity test using the insect baiting method against Tenebrio molitor larvae. A total of 59 endophytic fungal isolates were successfully obtained, of which 19 isolates showed pathogenic activity against T. molitor. Isolate EK2_23 (Beauveria sp.) showed the highest performance with mortality and mycosis of 85% and 100%, respectively. Morphological identification revealed the presence of four main genera: Beauveria, Metarhizium, Aspergillus, and Trichoderma. This finding confirms that corn endophytic fungi have the potential to be a prospective source of local biological agents for development as mycoinsecticides to control major corn pests.